Metabolomic characterization of human hippocampus from drug‐resistant epilepsy with mesial temporal seizure. (17th January 2018) - Detour, Julien; Bund, Caroline; Behr, Charles; Cebula, Hélène; Cicek, Ercument A.; Valenti‐Hirsch, Maria‐Paola; Lannes, Béatrice; Lhermitte, Benoît; Nehlig, Astrid; Kehrli, Pierre; Proust, François; Hirsch, Edouard; et al.
Summary: Objective: Within a complex systems biology perspective, we wished to assess whether hippocampi with established neuropathological features have distinct metabolome. Apparently normal hippocampi with no signs of sclerosis (noHS), were compared to hippocampal sclerosis (HS) type 1 (HS1) and/or type 2 (HS2). Hippocampus metabolome from patients with epilepsy‐associated neuroepithelial tumors (EANTs), namely, gangliogliomas (GGs) and dysembryoplastic neuroepithelial tumors (DNTs), was also compared to noHS epileptiform tissue. Methods: All patients underwent standardized temporal lobectomy. We applied 1 H high‐resolution magic angle spinning nuclear magnetic resonance (HRMAS NMR) spectroscopy to 48 resected human hippocampi. NMR spectra allowed quantification of 21 metabolites. Data were analyzed using multivariate analysis based on mutual information. Results: Clear distinct metabolomic profiles were observed between all studied groups. Sixteen and 18 expected metabolite levels out of 21 were significantly different for HS1 and HS2, respectively, when compared to noHS. Distinct concentration variations for glutamine, glutamate, and N ‐acetylaspartate (NAA) were observed between HS1 and HS2. Hippocampi from GG and DNT patients showed 7 and 11 significant differences in metabolite concentrations when compared to the same group, respectively. GG and DNT had a clear distinct metabolomic profile, notably regarding choline compounds, glutamine, glutamate, aspartate, and taurine. Lactate and acetate underwent similar variations in both groups. Significance: HRMAS NMR metabolomic analysis was able to disentangle metabolic profiles between HS, noHS, and epileptic hippocampi associated with EANT. HRMAS NMR metabolomic analysis may contribute to a better identification of abnormal biochemical processes and neuropathogenic combinations underlying mesial temporal lobe epilepsy.